SNAP MOR (TRADISI PENANGKAPAN IKAN MASYARAKAT BIAK) - Romarak Ap, Alfasis (JURNAL ILMU BUDAYA, 2018)
The purpose of this research is to find out the tradition of looking for fish for breeders by taking a mor snap. This research was carried out in Biak Island and was used to use purposive sampling technique, to obtain samples which are communities from urban coastal areas and rural coasts in Biak Island who know about the tradition of snap mor. This study concludes that the tradition of snap mor conducted by the Biak community has ways and techniques of fishing through the snap mor tradition that is adjusted based on the local wisdom of each region that has been studied from generation to generation.